Drought stress affects physiological parameters but not tuber yield in three Andean potato (iSolanum tuberosum/i L.) cultivars (2017)
This study evaluated the effect of water deficit on the physiological response and yield of three Andean potato cultivars. Leaf water potential (Ψw), soil matric potential (SMP), photosynthesis (A), stomatal conductance (gs), transpiration (E), intrinsic water use efficiency (WUEi), leaf temperature (LT), chlorophyll fluorescence parameters, chlorophyll (Chl), carotenoids (Car), electrolyte leakage (EL), growth and yield (Y). Parameters were determined in well-watered (WW) and drought-stressed (DS) plants. The three DS cultivars showed a decrease in leaf Ψw from the first day of treatment and reached values close to -2.00 MPa 4 days after treatment (DAT) for the Diacol Capiro (DC) cultivar, 5 DAT for the Pastusa Suprema (PS) cultivar and 6 DAT for the Esmeralda (Es) cultivar. The values of A, gs and E in the DS cultivars decreased from the first DAT. The LT reached the highest values when gs showed the lowest values for the three DS cultivars. WUEi was higher in Es under DS plants but lower in DC under DS. The PSII photochemical efficiency (Fv/Fm) showed values greater than 0.8 for all DS cultivars under DS, suggesting the absence of non-stomatal limitations for A. The Chl content increased in the Es cultivar under DS from 5 to 7 DAT compared to WW plants. Carotenoids (Ca) contents, the Car/Chl ratio, and EL increased in the three DS cultivars. There were no differences in yield and growth parameters between WW and DS cultivars. These results suggest that the three cultivars developed mechanisms to overcome the stress. One of these mechanisms could be the early synthesis of Car, which may maintain photosystem II function under water stress.